Morphology, diet, and population structure of the southern white-lipped mud turtle Kinosternon Leucostomum Postinguinale (Testudines: Kinosternidae) in the Nus River Drainage, Colombia (2016)
ABSTRACT: Most existing studies on the White-lipped Mud Turtle, Kinosternon leucostomum, have been based on northern Central American populations, leaving a lack of information on populations from southern Central America and South America. Herein we studied morphology, diet, and population structure of a population of the southern Kinosternon leucostomum postinguinale inhabiting four creeks in Colombia. Observed habitats used were highly variable, ranging from relatively clean waters to streams used for sewage disposal of wastewater from a human settlement. Body size was smaller than that of other populations of southern K. l. postinguinale and also than that of the northern K. l. leucostomum. Sexual dimorphism was evident, with males heavier, longer, and wider than females. Body size was associated with the habitat of origin, with Barrio Nuevo individuals being the largest. The main components of the diet were plant material, insects, snails, and algae. We did not find evidence of sexual differences in the diet, but we found geographic differences in the body size. The population with the largest individuals, from Barrio Nuevo Creek, consumed more snails while those from Totumo Creek, the population with the smallest individuals, consumed more ants and plant material as compared to the other creeks. Additionally, we found a highly male-biased sex ratio, with 2.5 adult males per female, very few juveniles, and no nests, which suggests a dangerous risk of population decline. We suggest continued monitoring of the demography of this population, emphasizing its reproductive biology.